Careful history taking detects initially unknown underlying causes of aspiration pneumonia. Issue 8 (6th July 2020) - Yoshimatsu, Yuki; Tobino, Kazunori; Ko, Yuki; Yasuda, Mina; Ide, Hiromi; Oku, Yoshitaka
Abstract : Aim: The majority of pneumonia in the elderly is attributed to aspiration. Identifying the cause of aspiration is essential for efficient treatment and prevention. However, the methodology on how to investigate the causes is not established. Therefore, we studied cases that were initially admitted for pneumonia and were newly diagnosed with an underlying cause of aspiration. This is the first study to analyze such cases collectively. Methods: This was a retrospective study. Patients aged 65 years or older admitted for pneumonia from October 2012 to November 2018 and were newly diagnosed with a cause of aspiration after admission was included. Patients were excluded if they had hospital‐acquired pneumonia, interstitial lung disease, or obstructive pneumonia or were immunocompromised. Results: In total, 4043 patients were admitted for pneumonia and 125 cases who were newly diagnosed with causes of aspiration after admission were included in the study. This constituted 30.7% of suspected aspiration pneumonia cases in which there was no known cause of aspiration on admission. The most common conditions newly identified were neurologic disorders, upper gastrointestinal disorders, drug‐induced conditions, and head and neck disease. Some were lethal. The diagnosis enabled treatment of the underlying condition and prevention of aspiration in most cases. The most common sign that lead to the diagnosis was symptoms seen from admission, followed by chronic symptoms. Conclusion: In 30.7% of those with suspected aspiration pneumonia with an unknown cause, a cause of aspiration was newly diagnosed. Careful history taking concerning neurological, gastrointestinal and drug‐induced disorders is essential in elderly patients with pneumonia. Geriatr Gerontol Int 2020; 20: 785–790 .